Tradescantia spathacea extract as biostimulating in growth and biological activities of Lactobacillus acidophilus and Lacticaseibacillus rhamnosus - Jaqueline Cruz-Maldonado; Jose Rodolfo Velazquez-Martinez; Cesar Orlando Pozo-Santiago; Juan Guzman-Ceferino; Angelica Alejandra Ochoa-Flores; Minerva Aurora Hernández-Gallegos (Ecosistemas y Recursos Agropecuarios)
Medicinal plants are an essential source of bioactive compounds with health benefits; however, their impact on probiotic properties remains largely unknown. The aim of this study was to evaluate the biostimulating effect of aqueous extracts of Tradescantia spathacea (EAT) on the development and probiotic properties of Lacticaseibacillus rhamnosus HN001 and Lactobacillus acidophilus La-14. For this purpose, the total phenol content (TPC), total flavonoid content (TFC), and antioxidant activity of EAT were evaluated by spectrophotometric methods (DPPH and ABTS). Subsequently, the biostimulating effect on the growth (BG), antimicrobial activity (AA), cholesterol consumption (CC), and biofilm formation (BFF) of Lacti. rhamnosus and Lacto. acidophilus were evaluated. The EAT presented a TPC of 68.98 ± 5.01 mg GAE g-1 dry extract and TFC of 4.54 ± 0.62 mg CE g-1 dry extract and antioxidant activity with IC50 values of 778.81 ± 60.80 and 4068.16 ± 206.8 µg mL-1, for DPPH and ABTS respectively. The correlation between CFT and antioxidant activity was low (r = -0.7948 and -0.7208; for DPPH and ABTS, respectively). In the BG study, the data showed that EAT stimulated the growth of Lacti. rhamnosus and Lacto. acidophilus and that AA was higher in biostimulated probiotic bacteria. However, CC and FBP were also stimulated by the symbiotic interaction between probiotics and EAT. The aqueous extract of T. spathacea had a biostimulating effect on the probiotic properties of Lacti. rhamnosus HN001 and Lacto. acidophilus La-14.